2023
DOI: 10.1111/imcb.12675
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced lupus progression in alcohol‐administered Fc gamma receptor‐IIb–deficiency lupus mice, partly through leaky gut‐induced inflammation

Wiwat Chancharoenthana,
Supitcha Kamolratanakul,
Phatcharapon Yiengwattananon
et al.

Abstract: Alcohol can induce a leaky gut, with translocation of microbial molecules from the gut into the blood circulation. Although the contribution of inflammation to organ‐mediated damage in lupus has been previously demonstrated, the mechanistic roles of alcohol consumption in lupus activation are not known. Herein, we tested the effects of 10‐week lasting alcohol administration on organ damages and immune responses in 8‐week‐old lupus‐prone Fc gamma receptor IIb–deficient (FcγRIIb−/−) mice. Our study endpoints wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 71 publications
(135 reference statements)
0
3
0
Order By: Relevance
“…At the phylum level, six (6/15) clinical studies [ 29–32 , 34 , 36 ] found a lower Firmicutes/Bacteroidetes (F/B) ratio in LN patients than in the HCs ( Figure 2 ). Four (4/14) clinical studies [ 32 , 33 , 36 , 37 ] and one (1/7) animal study [ 43 ] found a higher abundance of Proteobacteria in LN patients than in HCs. At the genus level, three (3/14) clinical studies [27, 35 , 39 ] found a higher abundance of Streptococcus in LN patients than in the HCs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the phylum level, six (6/15) clinical studies [ 29–32 , 34 , 36 ] found a lower Firmicutes/Bacteroidetes (F/B) ratio in LN patients than in the HCs ( Figure 2 ). Four (4/14) clinical studies [ 32 , 33 , 36 , 37 ] and one (1/7) animal study [ 43 ] found a higher abundance of Proteobacteria in LN patients than in HCs. At the genus level, three (3/14) clinical studies [27, 35 , 39 ] found a higher abundance of Streptococcus in LN patients than in the HCs.…”
Section: Resultsmentioning
confidence: 99%
“…was found to be higher in the LN group than in the control group in one (1/14) clinical study [ 28 ] and two (2/5) animal studies [ 28 , 41 ], but one (1/7) animal study [ 44 ] found a lower abundance. The genus Lactobacillus and species Lactobacillus reuteri ( L. reuteri ) were mentioned as having changes in abundance in two (2/14) clinical studies [ 32 , 38 ] and three (3/7) animal studies [ 38 , 42 , 43 ]. The results with consistent variation in bacterial abundance were extracted to draw a phylogenetic diagram ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation